Research progress on bacterial outer membrane vesicles in antibiotic resistance and clinical anti-infective therapy - Lu, Yukang; Wen, Zhenzhen; Liu, Xiaoyan; Zhang, Tingting; Liu, Meijin; Zhang, Linghan; Qiu, Jinyou; Wang, Maoyuan (Frontiers in Microbiology, 2025)
In recent years, bacterial outer membrane vesicles (OMVs)—nanoscale, bilayered membrane structures secreted by Gram-negative bacteria—have attracted considerable attention for their involvement in antibiotic resistance and potential in clinical anti-infective strategies. OMVs encapsulate diverse biomolecules, including proteins, lipids, toxins, and nucleic acids, thereby serving as critical mediators of communication between bacteria and host cells. They contribute to horizontal gene transfer, signal transduction, and biofilm formation, ultimately enhancing bacterial adaptability and resistance. Clinically, OMVs are regarded as promising therapeutic platforms owing to their excellent biocompatibility and intrinsic immunogenicity, with ongoing investigations exploring their roles in vaccine development, targeted drug delivery, and immune modulation. This review highlights the participation of OMVs in resistance mechanisms across common pathogenic bacteria and discusses their emerging applications in infection control. By elucidating the biogenesis and functional mechanisms of OMVs, novel antibacterial strategies may be developed, offering new avenues to address the escalating global challenge of antibiotic resistance.